2021
DOI: 10.4143/crt.2020.1060
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Stratification of Patients with Burkitt Lymphoma Using Serum β2-microglobulin Levels

Abstract: Purpose We aimed to investigate the prognostic value of serum β2-microglobulin for patients with Burkitt lymphoma (BL) and to propose a risk-stratifying classification system.Materials and Methods A prospective registry-based cohort study of BL patients treated with dose-intensive or effective dose-adjusted chemotherapies (n=81) was conducted. Survival outcomes were compared based on previously reported risk groups and/or serum β2-microglobulin levels. A risk-stratifying classification system incorporating ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…18 B2M is used as a predictive factor for tumor responsiveness to treatment and relapse, and the prognostic value of B2M in multiple hematological disorders was investigated in previous studies. [18][19][20] Previous studies confirmed the use of B2M as a prognostic and treatment failure factor in MCL. 21,22 Consistent with previous findings, B2M was an important component in our prognostic model.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…18 B2M is used as a predictive factor for tumor responsiveness to treatment and relapse, and the prognostic value of B2M in multiple hematological disorders was investigated in previous studies. [18][19][20] Previous studies confirmed the use of B2M as a prognostic and treatment failure factor in MCL. 21,22 Consistent with previous findings, B2M was an important component in our prognostic model.…”
Section: Discussionmentioning
confidence: 79%
“…The B2M level may be an immunological risk marker associated with survival 18 . B2M is used as a predictive factor for tumor responsiveness to treatment and relapse, and the prognostic value of B2M in multiple hematological disorders was investigated in previous studies 18–20 . Previous studies confirmed the use of B2M as a prognostic and treatment failure factor in MCL 21,22 .…”
Section: Discussionmentioning
confidence: 93%
“…KPS is generally completed at the time of admission assessment, which can easily reflect the patients' physical condition. b2-MG, which reflects the patient's tumor burden, can be obtained by peripheral blood tests (37)(38)(39), while SIRI can be calculated by complete blood count. Our study has shown that the four variables of Xijing model are all related to the prognosis of PCNSL patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] In addition, LDH and β2-MG are often present with varying degrees of elevation. [ 18 , 19 ] Positive EBV nucleic acid and elevated indicators such as lactate dehydrogenase and β2-MG were seen during the course of the disease. A case report [ 20 ] describes a 15-year-old boy, 3.5 years post-transplant with chronic EBV viremia, whose urinary CXCL10/Cr level increased acutely to 79.43 ng/mmol, 0.8 months prior to onset of BL.…”
Section: Discussionmentioning
confidence: 99%